Design Science Research in Information Systems. Advances in Theory and Practice 7th International Conference, DESRIST 2012, Las Vegas, NV, USA, May 14-15, 2012. Proceedings - Peffers, Ken.; Rothenberger, Marcus; Kuechler, Bill.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 7th International Conference on Design Science Research in Information Systems and Technology, DERIST 2012, held in Las Vegas, NV, USA, in May 2012. The 24 revised full papers presented together with 7 revised short papers were carefully reviewed and selected from 44 submissions. The papers are organized in topical sections on DSRIS in practice, DSRIS methodologies and techniques, social and environmental aspects of DSRIS, theory and theory building in DSRIS, and evaluation of DSRIS projects.
Keywords: Computer science; Computer communication systems; Software engineering; Information storage and retrieval; User interfaces (Computer systems).; Artificial intelligence; Computer Science; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; User Interfaces and Human Computer Interaction; Computer Communication Networks; Information Storage and Retrieval; Software Engineering; Electronic books